2010
DOI: 10.1016/j.ocecoaman.2010.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The ecological and economic value of cold-water coral ecosystems

Abstract: Despite the growing scientific literature on cold-water corals (CWC) there appears to be no studies that address the economic values or economic management of the resource. This paper presents an overview of the goods and services of CWC and their associated biodiversity. Use and non-use values associated with CWC are presented, and the methods relevant for assessing their valuation are discussed. The impact of human induced disturbance on CWC is reviewed, in order to indicate how knowledge of CWC values can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 127 publications
0
33
0
1
Order By: Relevance
“…We are also showing separately the distribution of CWC (Fig. 3), which are considered on a global scale among the most ecologically and economically valuable deep-water ecosystems (Roberts et al, 2009;Foley et al, 2010). Additionally, their carbonate exoskeleton permits keeping memory on former CWC presence at sites where they are either at present disappeared or waning (Delibrias and Taviani, 1985;Remia and Taviani, 2005;McCulloch et al, 2010;Malinverno et al, 2010).…”
Section: Resultsmentioning
confidence: 93%
“…We are also showing separately the distribution of CWC (Fig. 3), which are considered on a global scale among the most ecologically and economically valuable deep-water ecosystems (Roberts et al, 2009;Foley et al, 2010). Additionally, their carbonate exoskeleton permits keeping memory on former CWC presence at sites where they are either at present disappeared or waning (Delibrias and Taviani, 1985;Remia and Taviani, 2005;McCulloch et al, 2010;Malinverno et al, 2010).…”
Section: Resultsmentioning
confidence: 93%
“…In these cases, canyons can provide supporting services in the form of habitat, food, and nursery areas for commercial species (see Section Supporting services). Another provisional service of submarine canyons is as a source for cold-water corals harvested for jewelry (Foley and Armstrong, 2010). Canyons can also be a source of genetic resources.…”
Section: Provisioning Servicesmentioning
confidence: 99%
“…Foley et al (2010) showed that identified ecosystem services connected to CWC are i) as 157 raw material and ornamental resources (direct use and option values), ii) habitat functions, including 158 refuge and nursery functions (indirect use values), and iii) non-use values. In the only previous SP 159 survey which has been implemented on CWC (Glenn et al, 2010), the effects of CWC-protection on 160 off-shore industrial activities was included.…”
mentioning
confidence: 99%